Sustainable Community Development Step 5: Identify Sources of Help - Mickie E. Swisher; Sandra Rezola; James Sterns (EDIS)
This document contains lists of resources for developing a sustainable community. There are two lists, one containing national resources and a second containing Florida resources.  This document is FCS7218-Eng, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, IFAS, University of Florida, Gainesville FL 32611. First published: September 2003.